BOOK REVIEW OF ALICE SEVOLD’S “THE LOVELY BONES” - PREDINA DINI, EMY (LANTERN (Journal on English Language, Culture and Literature), 2015)
Each human being has different life journey and experiences. In this life, sometimes there are times when people feel happiness, excitement, joy, the warmth of love, and perfection. However, there are also times when people feel the opposite, such as falling into ruin, sadness, sorrow, grief, pain and suffering. When people feel one of all those things, they need the touches of others in order to share and get through it. One of the touches that people really need is love.